SELF-ABSORPTION CORRECTIONS BASED ON MONTE CARLO SIMULATIONS - Kamila Johnová (Acta Polytechnica CTU Proceedings, 2016)
The main aim of this article is to demonstrate how Monte Carlo simulations are implemented in our gamma spectrometry laboratory at the Department of Dosimetry and Application of Ionizing Radiation in order to calculate the self-absorption within the samples. A model of real HPGe detector created for MCNP simulations is presented in this paper. All of the possible parameters, which may influence the self-absorption, are at first discussed theoretically and lately described using the calculated results.